INTEGRASI ORKESTRASI PEMASARAN DENGAN FILOSOFI DWI SAPTA PADA KASUS VASELINE HEALING PROJECT - Laurensia, Bella; Sitanggang, Hot Junita; Marta, Rustono Farady; Daniar, Agus; Menayang, Alfred Pieter (Jurnal Komunikasi Nusantara, 2020)
Integrated Marketing Communication as a form of marketing communication strategy in order to build trust, maintain relationships with consumers and stakeholders and benefit the brand. This study aims to determine the application of marketing orchestration in Vaseline activities and the application of the Dwi Sapta Philosophy in Vaseline marketing communication. This type of research is descriptive qualitative using the case study method. Vaseline held a "Vaseline Healing Project" to improve the quality of life of people and provide skin care to the community. Vaseline consistently provides the best for its consumers, ranging from product variations, product quality to the services provided through training of medical personnel and also the mission of improving the skin condition of the community.